2012
DOI: 10.1177/1745691611427305
|View full text |Cite
|
Sign up to set email alerts
|

Pupillometry

Abstract: The measurement of pupil diameter in psychology (in short, "pupillometry") has just celebrated 50 years. The method established itself after the appearance of three seminal studies (Hess & Polt, 1960, 1964; Kahneman & Beatty, 1966). Since then, the method has continued to play a significant role within the field, and pupillary responses have been successfully used to provide an estimate of the "intensity" of mental activity and of changes in mental states, particularly changes in the allocation of attention an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
400
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 743 publications
(410 citation statements)
references
References 112 publications
(140 reference statements)
9
400
1
Order By: Relevance
“…Pupils dilate more to sexual stimuli depicting an individual's preferred sex than to stimuli of the other sex or to non-sexual stimuli (Hess & Polt, 1960;Hess, Seltzer, & Shlien, 1965;. In fact, dilation to sexually preferred stimuli appears to be the strongest pupillary response elicited by stimuli (Laeng et al, 2012). In addition, degree of pupil dilation corresponds with time spent viewing these stimuli, self-reported sexual attraction to stimuli, and selfreported sexual orientation (Hess et al, 1965;.…”
Section: Measurement Of Sexual Arousalmentioning
confidence: 99%
See 1 more Smart Citation
“…Pupils dilate more to sexual stimuli depicting an individual's preferred sex than to stimuli of the other sex or to non-sexual stimuli (Hess & Polt, 1960;Hess, Seltzer, & Shlien, 1965;. In fact, dilation to sexually preferred stimuli appears to be the strongest pupillary response elicited by stimuli (Laeng et al, 2012). In addition, degree of pupil dilation corresponds with time spent viewing these stimuli, self-reported sexual attraction to stimuli, and selfreported sexual orientation (Hess et al, 1965;.…”
Section: Measurement Of Sexual Arousalmentioning
confidence: 99%
“…Other research suggests that pupil dilation reflects attention that is likely not in the conscious control of participants (Heaver & Hutton, 2011). For these reasons, pupil dilation has been used as an indicator of automatic responses, including responses reflecting sexual arousal (Goldinger & Papesh, 2012;Laeng, Sirois, & Gredebäck, 2012). Pupils dilate more to sexual stimuli depicting an individual's preferred sex than to stimuli of the other sex or to non-sexual stimuli (Hess & Polt, 1960;Hess, Seltzer, & Shlien, 1965;.…”
Section: Measurement Of Sexual Arousalmentioning
confidence: 99%
“…Among them, the pupillary response can provide information about the time course of the cognitive phenomenon under study. It is also sensitive to processes that are only partially activated, never passing the threshold for eliciting overt behavior or for reaching consciousness (Laeng et al, 2012). Another remarkable property is that it is not affected by a participant's strategies, because it is quite difficult to control voluntarily.…”
mentioning
confidence: 99%
“…In another study, Hupé et al recorded pupil responses while their participants continuously reported changes in the perception of visual ambiguous stimuli, observing that 70% of pupil dilation could be accounted for by the motor response. A possible explanation for these findings is that the pupillary response is closely linked with the activity of the locus coeruleus (see Laeng et al, 2012, for a review), a subcortical structure involved in a large variety of processes, including task-related decision processes and the execution of behavioral responses. Thus, any change in the activity of the locus coeruleus due to planning or executing a response may have an effect on the pupillary response (Hupé et al, 2009).…”
mentioning
confidence: 99%
“…This method exploits the pupillary dilation (enlargement) that accompanies effortful mental activities, such as arithmetic (reviewed in Laeng, Sirois, & Gredebäck, 2012). Participants were first asked a yes/ no question, and then sequentially shown two response options ('yes' followed by 'no', or vice versa; each option was shown once).…”
mentioning
confidence: 99%